Os italianos em salto: associativismo, política e nacionalismo entre 1922 e 1942 - Santos, Otavio Gentil Dos [UNIFESP] (2020)
This essay proposes an analysis of identity transformations of the Italian immigrants and their offspring in the city of Salto in the state of Sao Paulo, Brazil from 1922 to 1942 (the fascist era) due to their change of politics of interests about immigrants living outside Italy in response to fascist ambitions for identity transformation. It seeks to understand how the structures created previously and later by immigrants and their offspring in this city also supported by the local Italian industry and the relationship with the receiving society works directly or indirectly for these fascist objectives. It also seeks to talk about questions like how the territoriality of these groups works like a speech template of the historical discourses and the construction city's historicity about this era and the echoes of this performed until today. The methodology included the analysis of journalistic material, primary sources and material written by memorialists, in addition to a bibliography on the subject.